The Correlation Between Students’ Motivation and Their Achievement in Studying English at a Junior High School in Samarinda - Gita Rininta Gita; Ida Wardani; Bibit Suhatmady; Yuni Utami Asih (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2025)
English plays a pivotal role as a global language and is taught as a compulsory subject in Indonesia. However, students’ low enthusiasm toward learning English remains a critical concern, particularly at the junior high school level. Motivation is widely recognized as a major determinant of success in second or foreign language learning. This study aims to investigate the correlation between students’ motivation and their English language achievement at a Junior High School in Samarinda. Employing a quantitative correlational method, the study involved 170 ninth-grade students selected through purposive sampling. Data were collected using a motivation questionnaire adapted from Gardner’s Attitude/Motivation Test Battery (AMTB) and English achievement scores provided by the school. Validity and reliability tests were conducted prior to data collection, with 11 out of 20 questionnaire items declared valid (r > 0.300) and Cronbach’s Alpha indicating reliable consistency (α = 0.701). Descriptive statistics revealed that the majority of students showed moderate motivation (37.1%) and high average English scores (M = 91.94). However, the results of the Spearman rank correlation showed a weak and negative correlation (r = -0.025, p = 0.747) between students’ motivation and English achievement. These findings suggest that although motivation exists, it is not a strong predictor of performance in this context. Other influencing factors such as teaching quality, parental involvement, and prior exposure to English may play a more significant role. This study highlights the need for a multifaceted approach in language teaching, addressing both motivational and environmental aspects to improve learning outcomes.